Planning the Plan: Around Works by Édouard Levé. Issue 1 (April 2019) - Tremblay, Thierry
Abstract : Drawing on Aristotle's concepts of energeia, dunamis, and ergon, this article attempts to articulate a typology of the different works described in Édouard Levé's Œuvres (2002 (French); 2014 (English)). This is carried out in the context of post-literary literature, i.e. following an aesthetics driven by the dismantling of 'qualities', understood as 'accidents', of literature's essence (literature's definition). It studies how Levé's work, and particularly his opus magnum Œuvres ( Works ), displays a series of short descriptive texts that intend to remain in their potentiality, while, at the same time, actualising this very potentiality (a potentiality 'in act', by an operation triggered in the reader's imagination). The question is therefore less the nature of fiction or 'what makes literature literature' than 'how does literature actualise its negation'.